The Effect of Knisley Learning Model to Improve Mathematical Problem-Solving Ability at MTs 'Aisyiyah North Sumatra - Damayanti, Rosdiyah; Ammy, Putri Maisyarah (EduMatika: Jurnal MIPA, 2022)
This study aims to determine the effect of the Knisley learning model to improve mathematical problem-solving skills at MTs'Aisyiyah North Sumatra and how influential the Knisley learning model is in improving mathematical problem-solving abilities. The researcher chose a sample of two classes, namely the control class and the experimental class, each with 25 people. The method used by the researcher is the experimental method. The research instrument used in this study was a test instrument which consisted of 5 questions. This research was conducted at MTs 'Aisyiyah North Sumatra in class VIII. Based on the results obtained based on the test results of the calculation of the hypothesis test, there are results thitung = 5.46 at a significant level = 0.005 and dk = n1 + n2 - 2 = 25 +25-2 = 48, then obtained ttable = 1.677. Based on the results of the calculation of the hypothesis test, it is obtained that thitung > ttable = 5.46 > 1.677, which means Ha is accepted and H0 is rejected.